Pengaruh PDRB, indeks pembagunan manusia dan zakat terhadap kemiskinan di Provinsi Jawa Tengah - Miftahussalam, Muhammad; Rofiuddin, Mohammad (Journal of Economics Research and Policy Studies, 2021)
This study aimed to determine the effect of GRDP, human development index, and zakat on poverty in Central Java Province. The object of this research is all regencies/cities in Central Java Province in 2015-2019. The method used to see effects using the panel data regression approach is the fixed effect model. The results in the study show that simultaneously zakat, GRDP, human development index affect poverty in Central Java Province. GRDP is not significant to poverty in Central Java Province. While the human development index and zakat decrease poverty in Central Java Province. The research model clarifies the role of zakat and human development in poverty alleviation in Central Java Province, so it is essential to maintain and increase its value over time to reduce poverty.